A Management perspective of CSR Reporting via Academic Entrepreneurship - Varghese, Dr. Titto (International Journal of Psychosocial Rehabilitation, 2020)
Corporate Social Responsibility (CSR) has much bigger implications for inclusive development of the any country. Industrial linkages of Academic Institutions are boosting entrepreneurial knowhow of the CSR Reporting practices. A systematic review of literature collected from Journals, Books, IT reports, Public documents and Economic survey reports were used for discussion. To relate fundamental business philosophy to make CSR sharper, smarter, and focused is what reallymatters and is the core part of any business in the 21st business philosophy century. Many companies have invested noted share of profits in various social development sectors. Also, there is research evidence to show that CSR work of the companies have reached where government could not reach so far in terms of financial Inclusion. However, there are some reports showing most of the companies have not even have CSR policies yet. All though various Indian corporate involved in CSR activities; it is not enough when contrast to their actual financial strength. This paper gives a solid background for the discussion about the possible role of CSR with respect to Social Inclusion